Estudos químicos e avaliação antioxidante, bactericida e larvicida do óleo essencial do Ocimum basilicum L (ALFAVACA) - Sousa, Manaces Cunha (2010)
This study aimed to investigate major metabolites from the aerial parts of Ocimum basilicum by a phytochemical screening. Quantitatively extracting the essential oil and subjecting it to thermal analysis and chromatography, as well as verifying its performance as an antioxidant, antibacterial and larvicidal agents. In this study it was observed that the aerial parts of Ocimum basilicum present tannins, depsides and depsidons, free steroids, flavonoids, saponins, flavonoid aglicons, triterpenoid aglicons, steroids and organic acids. The yield of essential oil extracted varied between 1.5 and 2.0% for the dried aerial parts, while the one of fresh aerial parts was between 0.28 to 1.0%. The study of essential oil plant species by gas chromatography coupled with mass spectrometry, revealed that the essence of it consists of six components, metilchavicol, linalool, eucaliptoll and farnesene, the main metabolites. The thermal study of the essential oil made by termogravimetry in air atmosphere and nitrogen, showed a similar thermal profile, indicating two mass loss attributed to volatilization of terpenes fraction and decomposition of aromatic fraction respectively. Antioxidant, antibacterial and larvicidal analysis revealed that the essential oil from dried aerial parts of Ocimum basilicum has outperformed the essential oil of fresh aerial parts when tested under the same conditions.